The clinical and radiological assessment of cyclic intravenous pamidronate administration in children with osteogenesis imperfecta - Adıyaman, Pelin; Öcal, Gönül; Berberoğlu, Merih; Evliyaoğlu, Olcay; Aycan, Zehra; Çetinkaya, Ergun (The Turkish Journal of Pediatrics, 2004)
Over the past 20 years, orally administered biphosphonates have been used extensively in the management of a number of common skeletal disorders of different etiology. Recently, in clinical practice, in a number of cases in whom oral therapy is insufficient or contraindicated, intravenous administration of pamidronate presents an alternative therapeutic option. In order to investigate the clinical and radiological effects of cyclic intravenous pamidronate administration in children with osteogenesis imperfecta, a prospective open study of pamidronate treatment was undertaken in a cohort of eight bed-bounded (3.6-13.8 years) patients with severe osteoporosis and vertebral deformities. Pamidronate was administered at a dose of 0.5 mg/kg/ day for three days. Tri-monthly cyclic intravenous infusions were performed over-one year. Bone density, verebral corpus heights, estimated volumetric bone density and biochemical measurements were analyzed. Side effects of the therapy were determined via questionnaire. Significant reductions in the number of bone fractures and pain were observed in all patients. Ambulation scores were significantly altered and seven of eight patients became independent. Serum alkaline phosphatase levels decreased significantly. Lumbar X-ray and densitometry showed a striking improvement by the end of the treatment period. Even spaced dense lines corresponding to infusion periods were observed on roentgenograms of the radio-ulnar region. Pubertal progression and growth velocity were not affected inversely during therapy. Although we did not observe any severe side effect, one patient’s blood urea nitrogen level was altered slightly. In conclusion, one year cyclical pamidronate treatment seems to be effective and safe in improving bone mineralization and in reducing fracture incidence in severe osteoporosis.